2017
DOI: 10.1038/srep40771
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of uteroplacental blood flow in IUGR indicates vortices and elevated pressure in the intervillous space – a pilot study

Abstract: Ischemic placental disease is a concept that links intrauterine growth retardation (IUGR) and preeclampsia (PE) back to insufficient remodeling of uterine spiral arteries. The rheological consequences of insufficient remodeling of uterine spiral arteries were hypothesized to mediate the considerably later manifestation of obstetric disease. However, the micro-rheology in the intervillous space (IVS) cannot be examined clinically and rheological animal models of the human IVS do not exist. Thus, an in silico ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…The model could be applied to compare normal and altered pregnancies, which may have different transfer efficiencies related both to changes in morphological structures and flow patterns. For example, in preeclampsia or intra uterine growth restriction (IUGR) the pressure in the intervillous space was estimated to be 5 to 10fold higher [13,18], and diabetic placentas display distinct differences in structure [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model could be applied to compare normal and altered pregnancies, which may have different transfer efficiencies related both to changes in morphological structures and flow patterns. For example, in preeclampsia or intra uterine growth restriction (IUGR) the pressure in the intervillous space was estimated to be 5 to 10fold higher [13,18], and diabetic placentas display distinct differences in structure [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in imaging technology have allowed 3D image based models to be developed. For example, maternal flow has been modelled to study the shear stress exerted by the maternal blood on the villous surface [12,13]. However, these studies did not include solute transport.…”
Section: Introductionmentioning
confidence: 99%
“…The five cases did not coincide with notch in uterine arteries. With a mathematical model, it has been demonstrated that the vessel wall shear stress and blood velocity jets are bigger in uterine arteries in IUGR and also vortices occur more often in the intervillous space [28]. This condition of increased turbulence with increased platelet count promotes the formation of microthrombus that explains the intervillous deposition of fibrin and increased placental weight related to birth weight in IUGR pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased wall shear stress is suggested to act at the villous surface in the inflow regions of the intervillous space, where high wall shear stress could damage the villous trophoblast or at least affect its cellular turnover. This disturbance may be reflected in enhanced trophoblast shedding and elevated levels of free fetal DNA in the maternal circulation [ 32 ]. Paradoxically, increasing shear stress has been suggested to have a protective effect against induced apoptotic death in trophoblast cell lines [ 18 ].…”
Section: The Influence Of Fluid Shear Stress On Trophoblast Turnovmentioning
confidence: 99%